Prevalence of Gingivitis and Its Impact on Diabetic and Non-Diabetic Patients in Zliten: A Gender-Based Comparative Study - Ben Aisha, Elham Mohammed; Algdar, Ahmed A.; Al-Rmely, Rahma Mansore; Al-Ayash, Majeda Yosef (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The study involved conducting oral examinations for diabetic patients at the Diabetes and Endocrinology Center in Zliten. The collaboration included dentists from the center. Additionally, a questionnaire was randomly distributed to patients visiting the Faculty of Oral and Dental Surgery. At the Diabetes and Endocrinology Center in Zliten, 85.4 % of the patients examined were diagnosed with diabetes. The majority of cases were among women, accounting for 87.5%, while men constituted 12.5%. Non-diabetic patients at the Faculty of Dentistry, gingivitis was attributed to other factors such as Calcium deficiency, Vitamin C deficiency, Vitamin D deficiency, and other underlying health issues. The high prevalence of diabetic patients with gingivitis at the Diabetes and Endocrinology Center highlights the importance of regular oral health check-ups and targeted preventive measures for diabetic individuals. For non-diabetic patients, addressing nutritional deficiencies and other underlying health conditions is crucial for preventing gingivitis. the study recommendations, for diabetic patients, regular dental check-ups, good oral hygiene practices, monitoring blood sugar levels, for Non-diabetic patients, addressing nutritional deficiencies, educating, patients about the importance of vitamins and minerals for oral health.
Keywords: Gingivitis; Diabetes; Vitamin C; Calcium; Vitamin D; Oral hygiene